2009
DOI: 10.1371/journal.pgen.1000369
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Multiple Sclerosis-Associated MHC Class II Allele HLA-DRB1*1501 Is Regulated by Vitamin D

Abstract: Multiple sclerosis (MS) is a complex trait in which allelic variation in the MHC class II region exerts the single strongest effect on genetic risk. Epidemiological data in MS provide strong evidence that environmental factors act at a population level to influence the unusual geographical distribution of this disease. Growing evidence implicates sunlight or vitamin D as a key environmental factor in aetiology. We hypothesised that this environmental candidate might interact with inherited factors and sought r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
315
3
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 467 publications
(348 citation statements)
references
References 42 publications
14
315
3
9
Order By: Relevance
“…Concordantly, several studies have found an inverse correlation between serum 25(OH)D concentration and disease activity in MS patients (Brola et al, 2016;Pierrot-Deseilligny, Rivaud-Péchoux, Clerson, de Paz, & Souberbielle, 2012;Rotstein et al, 2015;Simpson et al, 2010). These findings are supported by genetic data showing that the MS susceptibility gene HLA-DRB1*1501 is regulated by a VDdependent promotor (Ramagopalan et al, 2009). …”
Section: Introductionsupporting
confidence: 52%
“…Concordantly, several studies have found an inverse correlation between serum 25(OH)D concentration and disease activity in MS patients (Brola et al, 2016;Pierrot-Deseilligny, Rivaud-Péchoux, Clerson, de Paz, & Souberbielle, 2012;Rotstein et al, 2015;Simpson et al, 2010). These findings are supported by genetic data showing that the MS susceptibility gene HLA-DRB1*1501 is regulated by a VDdependent promotor (Ramagopalan et al, 2009). …”
Section: Introductionsupporting
confidence: 52%
“…117 We have recently shown how genetic variation defines a functional VDRE in the proximal promoter of HLA-DRB1 ( Figure 5). 118 Strikingly, this VDRE showed haplotype-specific differences, being highly conserved in the major MS-associated haplotype HLA-DRB1*1501 in Northern European populations, but disrupted to varying degrees in non-disease associated haplotypes. Functional assays showed that this VDRE can influence gene expression, conferring vitamin D sensitivity to the HLA-DRB1*1501 haplotype.…”
Section: Environmental Factors In Mhc Class II Gene Regulationmentioning
confidence: 93%
“…Multiple studies showed that 25-OH vitamin D levels are lower in MS cases compared to controls in both European-descended and African American populations (Munger et al, 2006;Islam et al, 2007;Gelfand et al, 2011;Ramagopalan et al, 2011b (Ramagopalan et al, 2009). Vitamin D receptor-binding elements have been identified in the majority of MS-associated genes, implying that expression of many of these genes could also be controlled by vitamin D (Ramagopalan et al, 2010).…”
Section: Vitamin D Geneticsmentioning
confidence: 99%